Brugada Syndrome: Presentation and Management of the Atypical Patient in the Emergent Setting - Alexander Nguyen; Mario Flores; Vilmogil Tano (Clinical Practice and Cases in Emergency Medicine, 2020)
Introduction: Brugada syndrome is a genetic disorder of the heart’s electrical system that increases a patient’s risk of sudden cardiac death. It is a syndrome most prevalent in Southeast Asians and is found 36 times more commonly in Asians than in Hispanics. Case Report: We report and discuss a case of a 68-year-old Hispanic male who presented with clinical and electrocardiogram abnormalities consistent with Brugada syndrome. Discussion: The patient’s age and ethnicity represents an atypical presentation of this rare syndrome and the lack of reported studies in the literature pertaining to these demographics reflect this. Conclusion: Further studies and characterizations are necessary as manifestations continue to be unearthed. As such, Brugada Syndrome should be considered in the differential diagnosis for a myriad of patient populations.